The Impact of Cement Industry Activity on The Environmental Quality of Settlements in Tipar Kidul Village, Ajibarang, Banyumas - Farah Khansabyla; Sri Rum Giyarsih (Geosfera Indonesia, 2024)
The quality of settlement environments surrounding industries is crucial as it reflects the living conditions affected by industrial activities. A study conducted in Tipar Kidul Village aimed to determine the impact of cement industry activities on the settlement environment. The method of this research uses survey within a multistage random sampling survey. The data collection uses interview. The data analysis is simple linear regression with the accuracy testing including validity, reliability, normality, and linearity tests. The research showed that a majority (62%) of the settlement environments conducted in medium-quality conditions. The researched showed industries play a significant role in taking negative impacts on settlements. Industries tend to make settlements uncomfortable to live in due to various activities. Moreover, a significant correlation was observed, indicating a significant influence with a very strong strength that 76.1% between the quality of settlement environments in Tipar Kidul Village and the activities of the cement industry. The cement industry activities impacted to settlement by affecting air pollution, noise from trucks, and machines. Corporate social responsibility program in Tipar Kidul Village included two program, funding program that gave 50.000 rupiah/person and in 2017 cement industry company helped Tipar Kidul Village to reconstruct along Tipar Kidul Village.